"Onde termina a justiça social e começa a subversão?" Igreja católica progressista e movimentos sociais no campo sob a vigilância do SNI na Paraíba (1975-1985) - Ferreira, Olga Larissa Veiga (2020)
This research addresses the work of the National Information Service (SNI) and its surveillance of the social movements in the countryside and the Catholic Church led by Archbishop Dom José Maria Pires, in the state of Paraíba during the ―slow, gradual and safe‖ transitional years of 1974-1985. Regarding the theoretical foundation, we utilized the concept of New Political History in dialogue with Social History or, as Barros (2012) pointed out, a social approach of the political. We also use the concepts of Antonio Gramsci, specifically the notions of organic intellect, private devices of hegemony and the theory of amplified state. Together with the approaches related to the question of Class as a process and formation of English historian Thompson (1987), to analyze the formation of the actions developed by workers in rural Paraíba, together with the social-political actions of the Chatolic Church in the state of Paraíba and, consequently, the vigilance endured by the SNI. The primary sources are the documents produced by the SNI - Agência Recife, together with the depositions conceded to the State Commission for the Truth and Memory Preservation of the state of Paraíba, in addition to the bibliographic productions about the period. This work is set in the area of concentration of History and Historical Culture, related to the line of research of History and Regionalities.